The Influence Of Liquidity, Profitability And Solvency On Financial Performance At The Autonomous Agent Indah Logistik Cargo Pajak Melati - Mery Cristina Simanullang; Geby Citra Ananda; Ramadhan Harahap (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of liquidity, profitability, and solvency on financial performance in the Autonomous Agent of Indah Logistics Cargo Pajak Melati. The research uses a quantitative approach with a causal research type, using secondary data in the form of corporate financial statements for the 2020–2024 period. The sampling technique used is saturated sampling, with multiple linear regression analysis method using SPSS version 22. The results showed that the liquidity proxied with the Quick Ratio could not be further analyzed because it experienced high multicollinearity (Tolerance 0.011; VIF 87,266). Profitability proxied by Return on Equity has a regression coefficient of –0.568 with a significance value of 0.167 (> 0.05), so it has no significant effect on financial performance. Meanwhile, solvency proxied by the Debt to Equity Ratio has a regression coefficient of 0.149 with a significance value of 0.013 (< 0.05), which shows a positive and significant influence on financial performance. Simultaneously, profitability and solvency had a significant effect on financial performance with an F value of 37.352 and a significance of 0.026 (< 0.05), and an Adjusted R Square value of 0.948. The conclusion of the study shows that the stability of the company's financial structure, especially from the aspect of solvency, has a more dominant role in supporting the improvement of financial performance than profitability.